Inappropriate prescribing among older persons in primary care: protocol for systematic review and meta-analysis of observational studies. Issue 2 (24th February 2017) - Lee, Cia Sin; Liew, Tau Ming
Abstract : Introduction: Inappropriate prescribing has a significant impact on older persons in primary care. Previous reviews on inappropriate prescribing included a heterogeneous range of populations and may not be generalisable to primary care. In this study we aim to conduct a comprehensive systematic review and meta-analysis of the prevalence, risk factors and adverse outcome associated with inappropriate prescribing, specifically among older persons in primary care. Methods and analysis: We will search PubMed, Embase, CINAHL, Web of Science, Scopus, PsycINFO and references of other review articles for observational studies related to the keywords 'older persons', 'primary care' and 'inappropriate prescribing'. Two reviewers will independently select the eligible articles. For each included article, the two reviewers will independently extract the data and assess the risk of bias using the Newcastle–Ottawa Scale. If appropriate, meta-analyses will be performed to pool the data across all the studies. In the presence of heterogeneity, meta-regression and subgroup analyses will also be performed. The quality of the evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Ethics and dissemination: The results will be disseminated through conference presentations and peer-reviewed publications. They will provide consolidated evidence to support informed actions by policymakers to address inappropriate prescribing in primary care, thus reducing preventable and iatrogenic risk to older persons in primary care. Trial registration number: CRD42016048874.